2020
DOI: 10.1177/1534735420972477
|View full text |Cite
|
Sign up to set email alerts
|

Protosappanin B Exerts Anti-tumor Effects on Colon Cancer Cells via Inhibiting GOLPH3 Expression

Abstract: Protosappanin B (PSB) is a key active component of Lignum Sappan extract. Although the antiproliferative effects of Lignum Sappan extract have been demonstrated in various cancer cells, relatively little is known about the effects of PSB on tumor progression. The aim of this study was to explore the anti-tumor effects of PSB on human colon cancer cells by regulation of intracellular signaling pathways and Golgi phosphoprotein 3 (GOLPH3) expression in vitro and in vivo. Our results showed that PSB effectively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In recent years, its anti-tumor properties have also been discovered. For instance, PSB can inhibit the proliferation of human bladder cancer cell lines and colon cancer cell lines [ 19 ]. To be specific, PSB inhibits the proliferation and promotes the apoptosis of human bladder cancer cells via interference with cell cycle regulation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, its anti-tumor properties have also been discovered. For instance, PSB can inhibit the proliferation of human bladder cancer cell lines and colon cancer cell lines [ 19 ]. To be specific, PSB inhibits the proliferation and promotes the apoptosis of human bladder cancer cells via interference with cell cycle regulation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…To verify the successful establishment of resistant cells, SW620 and LOVO cells were treated with 5-FU (0, 4, 8, 16, 32, and 64 μM; Nanjing Chia-Tai Tianqing Pharmaceutical Company) along with resistant cells to establish cell viability [ 19 ]. Appropriate concentrations of PSB were screened for subsequent experiments by treating 5-FU SW620 and 5-FU LOVO cells with different concentrations of PSB (Shanghai Yuanye Bio-Technology Company) to measure cell viability.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When Golgi apparatus stress is ameliorated, GOLPH3 expression decreases, and the phosphorylation of the PI3K/Akt/mTOR pathway is promoted [ 62 ]. Previous studies that found GOLPH3 promotes Akt in colon cancer were performed using the cell lines HCT-116 [ 40 ], LoVo [ 58 ], and SW620 [ 63 ]. To the best of our knowledge, no study has constructed and used GOLPH3-overexpressing and -silenced cell lines to investigate the impact of GOLPH3 on Akt in HCT-116 and HT-29 cells.…”
Section: Discussionmentioning
confidence: 99%